Monthly Production of Anthracite Coal, and Shipments and Production of Beehive Coke - Tryon, F. G. (The Review of Economics and Statistics, 1926)
FROM historical data recently collected it is now possible to carry the record of monthly production of coal back to January I905 and the monthly production of beehive coke back to I897. The figures are comparable with the current statistics now published by the Bureau of Mines (formerly by the United States Geological Survey). The continuous monthly series over the longer period may be of interest to students of the business cycle and the figures are here presented without analysis in order to make them promptly available. The Bureau's estimates of weekly and monthly production are based upon (i) complete and detailed annual reports from all producers, and (2) current reports of coal loaded for shipment by the principal rail and water carriers, the relation of which to the total production has been recorded for several years. The method of estimate was explained in the Journal of the American Statistical Association (September I920, pp. 3I4-25). That the shipments furnish a substantial basis for estimating the total output is seen from the following: production fluctuates directly with the shipments and either production or shipments will suffice as a measure of the activity of the anthracite industry. Of the two items, production is preferable because it may be added to bituminous coal production to get the total output of all coal in the country. For this reason and because the present record of shipments is not exactly comparable with the one formerly kept by the Anthracite Bureau of Information, now unfortunately discontinued, the Bureau of Mines will hereafter publish the current production rather than the shipments. The figures from January I905 to December I925 are given in Table i. For bituminous coal the problem is not so simple because of the conversion of coal into coke in beehive ovens located at the mines. The quantity so used fluctuates independently of either total production or of shipments of raw coal, and this makes it necessary to determine the current production of beehive coke as an incident to estimating the production of bituminous coal. This has led the Bureau of Mines to carry its record of monthly beehive coke production back to I897. The figures for I897 to I926 are given in Table 2. Data beginning with I9I2 had previously been published in Mineral Resources of the United States, I923 (Part II, p. 437). For those who may wish them, the records of shipments of beehive coke from the District, as reported by the Courier and an earlier newspaper, are given in Table 3. These records are available back to January I894. The Courier's figures have long been accepted by the trade as reliable, and they agree fairly well with the official government returns. It should be noted, however, that for the period I9OI-06 they also include the shipments from the small Upper Connellsville district and are not exactly comparable with the other years. For the early years shown in Tables 2 and 3, beehive coke was probably a good business indicator, though it simply reproduced the DISPOSITION OF COAL PRODUCED IN THE UNITED STATES IN I923, A TYPICAL YEAR